Oral health status of elementary-school children varied according to school they attended - Sri Widiati; Al Supartinah Santosa; Yayi Suryo Prabandari; Johana Endang Prawitasari (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Oral health has been promoted in elementary school. Oral health status is worsening among children aged 12 in Indonesia. Schools are an ideal social environment where dental health promotion strategies could be implemented to improve children’s oral health and to develop lasting good oral health behavior. Purpose: This study aimed to determine the association of sex, age, oral health behavior (tooth brushing practice, eating sweets and snacks, and routine dental health care visit) and family support, with oral health status among elementary school-children. Method: A school-based survey was carried out in 45 public elementary schools served by15 community health centers in Sleman, Yogyakarta. All fifth grade students (a total of 1191 students) in the schools were recruited as study participants after informed consent being given to parents. Questionnaires on health behavior and family support were administered to students, and examinations for OHIS and DMF-T were conducted by trained research assistants. Regression analyses (with R) were performed to identify whether sex, age, oral health behavior, family support and schools were significant determinants of oral health. Result: Females had higher DMF-T compared to males (1.93 vs 1.56), older children showed higher DMF-T. Effects oral health behavior and family support on OHIS and DMF-T were not significant after adjusting for school. School was significantly associated with OHIS and DMF-T. Conclusion: Sex and age were determinants of DMF-T. Oral health behavior and family support were not associated with OHIS and DMF-T. School was a consistent predictor of OHIS and DMF-T. School-based programs, especially targeted to certain schools with worse oral health, should be strengthened.